2018
DOI: 10.5812/iranjradiol.68250
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Manifestations of Cerebral Venous Thrombosis: Are There Any Differences According to Presence or Absence of Cortical Vein Involvement?

Abstract: Background: Cerebral venous thrombosis (CVT) is difficult to diagnose because of the variety of its clinical and imaging findings and the many anatomical variations in the cerebral venous system. Objectives: We aimed to investigate the clinical and radiological CVT and to evaluate differences in their findings, according to the presence or absence of cortical vein involvement (CVI). Patients and Methods: From the 13 years database of our institution, forty-nine patients were enrolled in the study. In all patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Superficial/cortical vein thrombosis appears as hyperdense cortical vessels on NECT, or the “cord sign.” Isolated cortical vein thrombosis has been considered rare (up to 5%) ( 7 ). In a retrospective analysis of 49 patients, Jang et al noted cortical veins as the most common site of CVT at 63%, followed by SSS at 61%, which may relate to SSS thrombosis as a frequent concomitant finding along with cortical vein thrombosis ( 7 , 12 ). SSS occlusion with extension to the cortical veins may present with edema and petechial hemorrhage with involvement of the cortex and subcortical white matter, as well as subarachnoid hemorrhage along the convexity ( 7 ).…”
Section: Classic Imaging Features Of Cvt and CVImentioning
confidence: 99%
See 2 more Smart Citations
“…Superficial/cortical vein thrombosis appears as hyperdense cortical vessels on NECT, or the “cord sign.” Isolated cortical vein thrombosis has been considered rare (up to 5%) ( 7 ). In a retrospective analysis of 49 patients, Jang et al noted cortical veins as the most common site of CVT at 63%, followed by SSS at 61%, which may relate to SSS thrombosis as a frequent concomitant finding along with cortical vein thrombosis ( 7 , 12 ). SSS occlusion with extension to the cortical veins may present with edema and petechial hemorrhage with involvement of the cortex and subcortical white matter, as well as subarachnoid hemorrhage along the convexity ( 7 ).…”
Section: Classic Imaging Features Of Cvt and CVImentioning
confidence: 99%
“…Another group found that the most recent patterns of parenchymal abnormalities in 44 consecutive patients hospitalized with CVT were HI (56.8%), ICH (22.72%), and NHI (20.45%) ( 9 ). Multiple other studies have addressed the anatomic distribution of CVI by frequency ( 1 , 2 , 4 , 5 , 12 ). Although most cases of sinus thrombosis involve multiple sinuses, the superior sagittal sinus (SSS) is the most common site of dural sinus thrombosis followed by the transverse sinus (TS) and sigmoid sinus (SS) ( 1 , 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation